Prognostic Role of the C-Reactive Protein/Albumin Ratio in Patients With Gynecological Cancers: A Meta-Analysis - Fang, Yingji; Zheng, Tingting; Zhang, Chengling (Frontiers in Oncology, 2021)
Background: Many studies have investigated the prognostic role of the C-reactive protein/albumin ratio (CRP/Alb ratio) in patients with gynecological cancers; however, there is lack of consensus owing to conflicting results across studies. We performed a meta-analysis to determine the prognostic role of the CRP/Alb ratio in gynecological cancers. Methods: We searched the PubMed, Embase, the Web of Science, Cochrane Library, China National Knowledge Infrastructure, and Wanfang electronic databases since inception to April 2021. Combined hazard ratios (HRs) and 95% confidence intervals (CIs) were used to estimate the prognostic effect of the CRP/Alb ratio in gynecological cancers. Pooled odds ratios (ORs) and 95% CIs were used to investigate the association between the CRP/Alb ratio and clinicopathological features. Results: The meta-analysis included seven studies with 1847 patients. The pooled results showed that a high pretreatment CRP/Alb ratio was associated with poor overall survival (HR 1.84, 95% CI 1.41–2.40, p<0.001) and progression-free /disease-free survival (HR 2.58, 95% CI 1.42–4.68, p=0.002). Additionally, a high CRP/Alb ratio was significantly associated with stages III-IV disease (the International Federation of Gynecology and Obstetrics classification) (OR 2.98, 95% CI 1.45–6.14, p=0.003). However, we observed a non-significant correlation between the CRP/Alb ratio and lymph node metastasis, tumor size, and histopathological grade. Conclusions: The CRP/Alb ratio is a convenient and accurate predictor of survival outcomes in gynecological cancers. A high CRP/Alb ratio also predicts tumor progression.